2019
DOI: 10.1371/journal.pone.0220341
|View full text |Cite
|
Sign up to set email alerts
|

An important role of cutaneous lymphatic vessels in coordinating and promoting anagen hair follicle growth

Abstract: The lymphatic vascular system plays important roles in the control of tissue fluid homeostasis and immune responses. While VEGF-A-induced angiogenesis promotes hair follicle (HF) growth, the potential role of lymphatic vessels (LVs) in HF cycling has remained unknown. In this study, we found that LVs are localized in close proximity to the HF bulge area throughout the postnatal and depilation-induced hair cycle in mice and that a network of LVs directly connects the individual HFs. Increased LV density in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…This co‐ordination is partially controlled by intrinsic properties of the HFSC, but is also reliant on the HF microenvironment, made up of surrounding cells and tissues that contribute to the HFSC niche . These cell types include the dermal papilla (DP), arrector pili muscle, adipose tissue, blood vessels and even lymphatics . Historically, immune cells have been described to be closely associated with hair follicles, with characteristic compositions at each stage of the hair cycle, but their influence on the HFSC niche has only recently been uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…This co‐ordination is partially controlled by intrinsic properties of the HFSC, but is also reliant on the HF microenvironment, made up of surrounding cells and tissues that contribute to the HFSC niche . These cell types include the dermal papilla (DP), arrector pili muscle, adipose tissue, blood vessels and even lymphatics . Historically, immune cells have been described to be closely associated with hair follicles, with characteristic compositions at each stage of the hair cycle, but their influence on the HFSC niche has only recently been uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocyte growth factor up‐regulates the expression of Tβ4 during angiogenesis, suggesting that hepatocyte growth factor may indirectly affect HF growth and development by enhancing the expression of Tβ4 or synergistically exerting biological effects with Tβ4 58,59 . Therefore, the cyclic circulation of the HF and the regulation of hair growth can be achieved indirectly through endogenous Tβ4‐dependent angiogenesis around the HF 54,60,61 …”
Section: Roles Of Endogenous Tβ4 In Hf Growth and Developmentmentioning
confidence: 99%
“…Notably, the increased expression of VEGF is induced by up‐regulation of hypoxia‐inducible factor 1 by Tβ4 54 . Moreover, the proliferation, migration, differentiation and angiogenesis of endothelial progenitor cells are realized by the activation of the phosphatidylinositol 3‐kinase (PI3K)/AKT/endothelial nitric oxide synthase signalling pathway by Tβ4 61 . Other studies have shown that the expression of VEGF is regulated by basic fibroblast growth factor (bFGF) 68 .…”
Section: Possible Signalling Pathways Of Tβ4 In Hf Growth and Developmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, CD31 + vasculature may inhibit HFSC activation in the hair germ possibly via signaling, but at the same time promote hair follicle growth fueled by transit‐amplifying matrix cells (Yano et al, 2001). While endothelial cells are often found to maintain the quiescence of other tissue stem cells such as muscle stem cells and neural stem cells (Azevedo et al, 2017; Verma et al, 2018), the role played by lymphatic endothelial cells is more controversial as the ablation of lymphatic vessels and genetically induced changes in lymphatic vessel showed highly mixed outcomes on HFSC behaviors (Gur‐Cohen et al, 2019; Peña‐Jimenez et al, 2019; Yoon et al, 2019a). Therefore, an urgent question for the field is to more precisely dissect the functions of each type of vasculature on HFSC activity.…”
Section: Introductionmentioning
confidence: 99%